2008
DOI: 10.1021/ja802102q
|View full text |Cite
|
Sign up to set email alerts
|

Nepheline from K2CO3/Nanosized Sodalite as a Prospective Candidate for Diesel Soot Combustion

Abstract: Nepheline group materials obtained by a thermal treatment of K2CO3-supported nanosized sodalite are identified as cost-effective materials which show promising activity and durability toward diesel soot combustion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(49 citation statements)
references
References 18 publications
4
45
0
Order By: Relevance
“…Generally, either using water washing [18,49,50] or exposure to water vapor [13,51] is considered to be evaluation methods of catalyst stability in diesel exhaust containing water. Comparatively, water washing is thought as a simple, but drastic mean [26] and thus was chosen in this work.…”
Section: Stabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, either using water washing [18,49,50] or exposure to water vapor [13,51] is considered to be evaluation methods of catalyst stability in diesel exhaust containing water. Comparatively, water washing is thought as a simple, but drastic mean [26] and thus was chosen in this work.…”
Section: Stabilitymentioning
confidence: 99%
“…Catalysts containing potassium (K) have attracted increasing attentions owing to their high activity for soot combustion [12][13][14][15][16][17][18]. Many groups [19][20][21][22][23] have done pioneering and extensive studies for this kind of catalyst system, including evaluation and screening of various catalytic materials, the effects of the soot-catalyst contact and mobility of catalysts, as well as the influence of supports, etc.…”
Section: Introductionmentioning
confidence: 99%
“…20.45 wt% for OAC, 8.01 wt% for CAC, 4.74 wt% for NAC in Table 1). Oxygen groups play a role of combustion-supporting agent in combustion engineering [31]. Thus, combustion is more sufficient with increasing oxygen content, resulting in exothermic peak shifts to lower temperature.…”
Section: Articlesmentioning
confidence: 99%
“…Recently, in order to get a highly active and stable catalyst, people began to investigate potassium containing compounds [6,25,26]. Okubo et al [26] have reported that potassium-enriched nepheline group materials exhibited excellent soot oxidation activity; and the highly improved oxidation activity was attributed to the major contribution of K species existing on the surface of nepheline group materials.…”
Section: Introductionmentioning
confidence: 99%
“…Okubo et al [26] have reported that potassium-enriched nepheline group materials exhibited excellent soot oxidation activity; and the highly improved oxidation activity was attributed to the major contribution of K species existing on the surface of nepheline group materials. In this point of view, those potassium containing compounds which are structurally stable in moist air and thermally stable at high temperature should be potential catalysts for soot oxidation.…”
Section: Introductionmentioning
confidence: 99%